STUDY OF BOMBAY PRAWNS The Seasonal Fluctuation and Variation in Abundance of the Commercially Important Species of Bombay Prawns with a Brief Note on Their Size, State of Maturity and Sex Ratio - Shaikhmahmud, F S; Tembe, V B (Indian Journal of Fisheries, 2015)
The present paper is the result of investigations carried out during the period July 1952 to July 1954 and deals with the study of commercially important species of prawns found in the inshore area of Bombay region and the seasonal fluctuations as well as the variation in abundance during the different months of the year. With the exception of the work done by Chopra (1943) and Rai (1933), practically no other information is available about the Prawn Fishery of Bombay, though much work has been done on the Prawn Fishery of Malabar Coast. In this connection, mention must be made of Panikkar (1937) and Menon (1953, 1955-57).